Koncepcja cyklu SAPE, czyli jak znaleźć to coś, czego nie dostrzegają inni - Paluchowski, Paweł (Idea of SAPE Cycle or How to Find that Something, that Others Cannot Notice, 2008)
In the past a day and night had "as much as" 24 hours. Now it is "only" 24 hours. In so rushing world adopting the attitude of active looking forward аяА quick, almost immediate reacting to appearing opportunities and threats can turn out as a key to success which is reaching a permanent competitive advantage. That is SAPE cycle indeed, which lies in sensing circumstances, anticipating appearing opportunities and threats, determine priorities and realize (execute) them. But SAPE cycle is not only a conception of strategic management. Above all that is a way of thinking. In this article the author tries to show and explain that idea especially against (or rather with) classic strategic management and give some examples of using it in practice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 287-295